2018
DOI: 10.5194/gmd-11-3369-2018
|View full text |Cite
|
Sign up to set email alerts
|

ORACLE 2-D (v2.0): an efficient module to compute the volatility and oxygen content of organic aerosol with a global chemistry–climate model

Abstract: Abstract. A new module, ORACLE 2-D, simulating organic aerosol formation and evolution in the atmosphere has been developed and evaluated. The module calculates the concentrations of surrogate organic species in two-dimensional space defined by volatility and oxygen-to-carbon ratio. It is implemented into the EMAC global chemistry-climate model, and a comprehensive evaluation of its performance is conducted using an aerosol mass spectrometer (AMS) factor analysis dataset derived from almost all major field cam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 86 publications
2
35
0
Order By: Relevance
“…Specifically, it has been estimated that BB emissions of primary OA (POA), which typically constitutes the predominant fraction of BB aerosol, contribute about 70 % of total POA emissions (Bond et al, 2013). In recent years, numerous studies have been aimed at investigating and modeling sources (e.g., May et al, 2013;Jathar et al, 2014;Konovalov et al, 2015;van der Werf et al, 2017), radiative effects (e.g., Saleh et al, 2013;Archer-Nicholls et al, 2016;Pokhrel et al, 2017;Yao et al, 2017), and atmospheric transformations (e.g., Cubison et al, 2011;Jolleys et al, 2012;Forrister et al, 2015;Shrivastava et al, 2015;Konovalov et al, 2015;Tsimpidi et al, 2018;Theodoritsi and Pandis, 2019 ) of BB OA and its components.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, it has been estimated that BB emissions of primary OA (POA), which typically constitutes the predominant fraction of BB aerosol, contribute about 70 % of total POA emissions (Bond et al, 2013). In recent years, numerous studies have been aimed at investigating and modeling sources (e.g., May et al, 2013;Jathar et al, 2014;Konovalov et al, 2015;van der Werf et al, 2017), radiative effects (e.g., Saleh et al, 2013;Archer-Nicholls et al, 2016;Pokhrel et al, 2017;Yao et al, 2017), and atmospheric transformations (e.g., Cubison et al, 2011;Jolleys et al, 2012;Forrister et al, 2015;Shrivastava et al, 2015;Konovalov et al, 2015;Tsimpidi et al, 2018;Theodoritsi and Pandis, 2019 ) of BB OA and its components.…”
Section: Introductionmentioning
confidence: 99%
“…The SVOCs and IVOCs can also be distributed between several model types, depending, e.g., on their oxidation state (O:C ratio), origin (e.g., primary or secondary, anthropogenic or biogenic, etc. ), and photochemical age (Donahue et al, 2012a,b;Shrivastava et al, 2013;Tsimpidi et al, 2018). Representing the processes involving SVOCs and IVOCs within the VBS framework has been shown to allow improving the performance of simulations of OA from vegetation fires with respect to simulations using the "conventional" OA modeling framework, in which these processes are basically disregarded and only specific volatile https://doi.org/10.5194/acp-2019-425 Preprint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the organic matter to organic carbon ratio (OM : OC) was first believed to lie between 1.2 and 1.4 (Grosjean and Friedlander, 1975), numerous studies (Turpin and Lim, 2001;El-Zanan et al, 2005;Aiken et al, 2008;Couvidat et al, 2012;Tost and Pringle, 2012;Canagaratna et al, 2015;Tsimpidi et al, 2018) show that OM : OC is approximately 1.6 for urban aerosols and 2.1 for non urban aerosols. Zhang et al (2005a) developed an algorithm to deconvolve the mass spectra of OAs obtained with an Aerodyne ™ aerosol mass spectrometer (AMS) in order to estimate the mass concentrations of hydrocarbon-like and oxygenated organic aerosols (HOAs and OOAs).…”
Section: Introductionmentioning
confidence: 99%
“…SOA is formed in the atmosphere when volatile organic molecules, emitted from both anthropogenic and natural sources, are oxidized and partition to the particle phase (Ervens et al, 2011;Hallquist et al, 2009). The exact chemical composition of SOA remains uncertain; however, measurements have shown that SOA contains 1000s of different organic molecules and the average oxygen-to-carbon (O:C) ratio of organic molecules in SOA ranges from 0.3 -1.0 or even higher (Aiken et al, 2008;Cappa and Wilson, 2012;DeCarlo et al, 2008;Ditto et al, 2018;Hawkins et al, 2010;Heald et al, 2010;Jimenez et al, 2009;Laskin et al, 2018;Ng et al, 2010;Nozière et al, 2015;Takahama et al, 2011;Tsimpidi et al, 2018). SOA also contains a range of organic functional groups including alcohols and carboxylic acids (Claeys et al, 2004(Claeys et al, , 2007Edney et al, 2005;Fisseha et al, 2004;Glasius et al, 2000;Liu et al, 2011;Surratt et al, 2006Surratt et al, , 2010.…”
mentioning
confidence: 99%